Who (or What) Can Do Psychotherapy: The Status and Challenge of Nonprofessional Therapies - Christensen, Andrew; Jacobson, Neil S. (Psychological Science, 1994)
Research suggests that paraprofessional therapists usually produce effects that are greater than effects for control conditions and comparable to those for professional therapist treatment Other nonprofessional psychological treatments, such as self-administered materials and self-help groups, have also demonstrated positive effects Because of the promise of these nonprofessional treatments, their potential for low-cost service delivery, and the important theoretical questions that studies comparing them can answer, psychotherapy outcome research should shift away from comparisons of different professional therapies and instead compare nonprofessional therapies with professional therapy